Making the Case for a Null Effects Framework in Environmental Education and K-12 Academic Outcomes: When “Just as Good” Is a Great Thing - Stevenson, Kathryn T.; Peterson, M. Nils; Carrier, Sarah J.; Strnad, Renee L.; Olson, Ryan A.; Szczytko, Rachel E. (Frontiers in Communication, 2019)
As K-12 audiences represent a major proportion of environmental education (EE) audiences, academics should be an outcome of interest in EE research and evaluation. However, research around links between EE and academic outcomes (e.g., grades, test scores) is scant. Reasons for limited research on EE and academic outcomes may include disinterest in academic outcomes, assertion that academic outcomes are poor measures of learning, and normative biases against publishing null or negative effects within academia. We argue for adoption of a null effects framework for linking EE and academic outcomes. We begin by outlining what we mean by a null effects framework and then suggest reasons why the EE community should adopt it. Specifically, a null effects framework embraces and celebrates research demonstrating no difference in traditional academic outcomes associated with EE curricula and more traditional classroom instruction. We describe key aspects of operationalizing a null effects framework, including use of key statistical procedures (e.g., measuring power), and changes in peer review associated with emphasizing measures of evidence beyond hypotheses testing and p values. We conclude by describing how this approach matches EE objectives, strengthens links to academic outcomes without being bound by them, avoids setting unrealistic expectations for EE, and highlights the myriad of non-academic co-benefits offered by EE. As including EE in schools is the best opportunity for reaching the most learners in terms of numbers and diversity, we offer a null effects framework as an approach that can boost adoption of EE where it is arguably needed most.